2021
DOI: 10.1200/jco.2021.39.15_suppl.tps1096
|View full text |Cite
|
Sign up to set email alerts
|

Trastuzumab deruxtecan (T-DXd) combinations in patients with HER2-positive advanced or metastatic breast cancer: A phase 1b/2, open-label, multicenter, dose-finding and dose-expansion study (DESTINY-Breast07).

Abstract: TPS1096 Background: HER2-targeted therapies have improved survival in patients (pts) with HER2+ advanced/metastatic breast cancer (mBC) but challenges remain, including resistance to current HER2-targeted therapies. Also, additional treatment options are needed in pts with brain metastases (BM). In the phase 2 DESTINY-Breast01 trial, T-DXd demonstrated efficacy, with an objective response rate (ORR) of 61.4% and median progression-free survival (mPFS) of 19.4 mo in pts with previously treated HER2+ advanced/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…At the time of writing, there are a number of clinical trials underway, evaluating T-DXd as a first line treatment, alone or in combination with pertuzumab, for HER2-positive advanced breast cancer (DESTINY-Breast07) 18 and DESTINY-Breast06 which directly compares standard-of-care chemotherapy to T-DXd for HR+/HER2-low or HR+/HER2-ultralow (defined as IHC 0 with minimal (<1+) membrane staining) advanced breast cancers after one or more lines of endocrine therapy. To date, both of these trials have shown improved outcomes for patients given T-DXd.…”
Section: Discussionmentioning
confidence: 99%
“…At the time of writing, there are a number of clinical trials underway, evaluating T-DXd as a first line treatment, alone or in combination with pertuzumab, for HER2-positive advanced breast cancer (DESTINY-Breast07) 18 and DESTINY-Breast06 which directly compares standard-of-care chemotherapy to T-DXd for HR+/HER2-low or HR+/HER2-ultralow (defined as IHC 0 with minimal (<1+) membrane staining) advanced breast cancers after one or more lines of endocrine therapy. To date, both of these trials have shown improved outcomes for patients given T-DXd.…”
Section: Discussionmentioning
confidence: 99%
“…T-DXd combinations are currently being investigated in ongoing clinical trials. The phase I/IIb Destiny-Breast07 trial is exploring various regimens, including combinations of T-DXd with paclitaxel for patients with HER2-positive mBC [ 53 ]. Additionally, another phase Ib study, Destiny-Breast08, will assess five different regimens, incorporating combinations of T-DXd with capecitabine, anastrozole, and fulvestrant in HER2-low mBC patients [ 54 ].…”
Section: Combinations In Clinical Development: Adcs Combined With Che...mentioning
confidence: 99%
“…However, in the overall population, there was increased toxicity with no clinically significant PFS prolongation [79]. The phase Ib/II DES-TINY-Breast07 study is currently investigating the addition of various combination partners, including the PD-L1 inhibitor durvalumab, to T-DXd [80].…”
Section: New Combination Therapiesmentioning
confidence: 99%
“…In der Gesamtpopulation zeigte sich jedoch keine klinisch bedeutsame PFS-Verlängerung bei gleichzeitig erhöhter Toxizität [79]. In der Phase-Ib/II-Studie DESTINY-Breast07 wird derzeit die Hinzunahme von verschiedenen Kombinationspartnern, einschließlich des PD-L1-Inhibitors Durvalumab, zu T-DXd untersucht [80]. Darüber hinaus bieten Kombinationen mit Inhibitoren des Phosphoinositid-3-Kinase(PI3K)/AKT-Kinase-Signalwegs insbesondere bei PIK3CA-mutierten Tumoren und überaktiviertem PI3K-Signaling, welches zu Anti-HER2-Resistenz führt, zusätzliche Therapieansätze.…”
Section: Neue Kombinationstherapienunclassified